Some of the content and length of employment contract, the written form of the contract and work book (Journal of actual problems of jurisprudence, 2019)
It is provided measures for consideration of the main problems arising in connection with validity period of the employmentcontract, creation of the individual employment contract, possibility of establishment of a probation period in case of acceptance forwork, contents of the individual employment contract according to the service record.